Developing In-House Training Module: The Excitement of Learning Media Through Canva to Enhance ICT Competency of Elementary School Teachers - Shofiah, Nyimas; Kesumawati, Nila; Harapan, Edi (Journal of Social Work and Science Education, 2025)
This study aims to: (1) analyze training models for enhancing information and communication technology (ICT) competency among elementary teachers, and (2) develop an In-House Training (IHT) module to improve ICT skills. Using Research and Development (R&D) methodology, the study progressed through three phases: preliminary research, module development, and testing. Fourteen teachers and principals from SD Negeri 38 Palembang participated as subjects. The study produced “The Excitement of Learning Media Through Canva”, a validated IHT module demonstrating high feasibility, with 88.54% (material experts) and 91.07% (media experts) approval rates. Practicality assessments rated the module 4.56/5 (very good), while effectiveness was confirmed by post-test scores averaging 90.66%. These results affirm the module’s validity, practicality, and effectiveness for teacher training. Novelty lies in the module’s integration of Canva as a user-friendly, creative tool for ICT skill development, tailored specifically for elementary educators. Practical implications include providing schools with a ready-to-implement, cost-effective training solution that enhances digital literacy. The study contributes to educational technology by offering a replicable model for teacher professional development, bridging the gap between ICT theory and classroom application. Future research could explore longitudinal impacts on teaching practices or adapt the module for diverse educational contexts.